Implementation of Least Significant Bit Steganography for Securing Electronic Land Certificates - M. Fadhil Lutfi; Moh. Ali Romli (Kirana Publisher (KNPub), 2025)
The government’s transition from physical to electronic land certificates raises significant concerns regarding document security and authenticity. This study implements the Least Significant Bit (LSB) steganography technique to secure electronic land certificates by embedding user identification and metadata into a digital image. The LSB method hides information within the least significant bits of image pixels, ensuring that the visual appearance of the image remains unchanged to the human eye. This approach enables the secure storage of sensitive data, allowing only authorized users to extract the hidden information for document verification. Experimental results demonstrate that the embedded image maintains high visual quality, as indicated by low Mean Squared Error (MSE) and high Peak Signal-to-Noise Ratio (PSNR) values. The LSB steganography technique thus provides an effective and imperceptible method for enhancing the confidentiality and integrity of electronic land certificates.